FEATURES OF THE LABOR MARKET FORMATION OF THE REGION - Альошина, Тетяна (Modern engineering and innovative technologies, 2023)
This article is concerned with the analyzes of theoretical aspects of the regional labor market, analyzes the definition of the essence of the regional labor market. The essence of a complete set of interconnected elements of the regional labor market is